3D bioprinting and decellularized ECM-based biomaterials for in vitro CV tissue engineering. Issue 2 (30th April 2018) - Das, Sanskrita; Jang, Jinah
Advanced extrusion-based 3D printing strategies allow the rapid fabrication of complex anatomically relevant architectures. Moreover, they have the potential to fabricate 3D-bioprinted cardiac constructs by depositing cardiac cells with appropriate biomaterials. Heart-derived decellularized extracellular matrices containing a complex mixture of various extracellular molecules provide a comprehensive microenvironmental niche similar to native cardiac tissue. Nonetheless, a major concern persists pertaining to insufficient vascularization and mimicking of the complex 3D architectural features, which can be tackled using 3D printing approaches. In this review, we discuss the advantage and application of decellularized extracellular matrix-based hydrogels for the 3D printing of engineered cardiac tissues. We also briefly talk about the integration of electroactive materials within cardiac patches to improve the myocardium's electrophysiological properties.